Evaluation of olfactory function in migraineurs during the migraine-free period with odor identification test - Tekeli, Hakan; Güney Şenol, Mehmet; Özdağ, Fatih; Saraçoğlu, Mehmet; Yaşar, Halit; Tansel Kendirli, Mustafa; Altundağ, Aytuğ; Çayönü, Melih; Salihoğlu, Murat; Türker, Türker (ENT Updates, 2014)
Objective: Despite the fact that there are many studies about the osmophobia and migraine, we have very little knowledge about the olfactory abilities of migraineurs during the period between the attacks. So, the aim of this study was to evaluate the olfactory function of migraineurs during the period without headaches with odor identification test. Methods: Two hundred and ninety healthy people aged 16 to 65 years (152 female, 138 male) and 84 migraine patients aged 18 to 55 years (47 female, 37 male) were studied. The participants with migraine were selected from the patients who applied to headache outpatient clinic for assessment. Participants, appropriate to the study, were physically and neurologically examined in detail and then they were taken to the test room in order to be screened with Short Smell Test Battery of GATA Haydarpaşa (GULTEST). Results: The mean GULTEST score of the migraine group was less than the healthy group and the difference was significant. The effect of gender, cigarette smoking and disease status (migraine) on GULTEST scores was evaluated by linear regression model. It was found that females had higher odor identification scores than males in both migraineurs and controls. On the other hand, cigarette smoking had a significant negative effect on GULTEST scores. Furthermore, migraine had a significant negative effect on GULTEST scores. Conclusion: Our study showed that even during the headache-free period, migraineurs might have reduced olfactory abilities.